Efficacy evaluation of 1,3-diary1 propenones as nitrification inhibitors - Shakil, Najam Akhtar; Kumar, Rajesh; Kumar, Jitendra; Saxena, Dinesh Bahudur (The Indian Journal of Agricultural Sciences, 2008)
A series of 1,3-diary1 propenones (substituted chalcones) has been synthesized and their per cent nitrification inhibition efficacy evaluated. The inhibitor effectiveness was evaluated on 4 parameters, namely concentrationof ammonium-N and nitrate-N, per cent nitrification inhibition, ratio of ammonium-N and nitrate-N, and total mineral N. It was observed that substituents at different positions in the phenyl rings affected the per cent nitrification inhibitor efficacy. The presence of halogen, hydroxy and methylene- dioxy groups greatly influence the nitrification inhibitory activity as evidenced in case of compounds 3-(4-chloropheny1)-1-phenyl-propenone (19), 3-(4-bromopheny1)-1-p-toly1-propenone (9), 3-(4- bromopheny1)-1-(4-methoxypheny1)-propenone (11), 3-(4-chloro pheny1)-1-(2,4-dihydroxypheny1)-propenone (12) and 3-(3,4-methylenedioxypheny1)-1-(2-hydroxypheny1)-propenone (15).